Arsitektur Bangunan Istana Maimun Telaah Sejarah dan Ornamen - Abdul Ghani Jamora Nasution; Agilia Febriani; Nadia Syafitri; Pramudia Ananda (CV. Aksara Global, 2023)
This Maimun Palace is the only and most prominent relic to show the existence of Malay culture in the city of Medan. When viewed from the shape and appearance of the Maimun Palace building, it has messages that are not directly visible, but in terms of visual communication, the Maimun Palace building also has a lot of information about the heyday, leadership and existence of the Malay Sultanate both in terms of appearance and the interior of the building. it has. This study aims to examine and describe the architecture of the Maimoon Palace building through historical and ornamental studies. This research was conducted in the Maimun Palace building located on Jalan Sultan Ma'moen Al Rasyid, Medan Maimun, Medan City with a qualitative descriptive research method. The type of data needed in this research is secondary. The results of this study indicate that the Maimun palace building is feasible for conservation.